FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WANITA USIA DALAM MELAKUKAN DETEKSI DINI KANKER SERVIKS DI DESA JATIMULYA WILAYAH KERJA PUSKESMAS PEDES KABUPATEN KARAWANG - Mardianti Mardianti (Jurnal Kebidanan, 2019)
Indonesia is a country in ASEAN which is ranked top for total deaths of cervical cancer in women and coupled with the number of new cases of about 20 cases per day, West Java ranked 5th with the number of cervical cancer cases as many as 5,786 people or around 11.78% . This incidence increased compared to the previous year which was around 10.38%. Based on data from the Karawang district health office early detection of cervical cancer with IVA examination as much as 10.2% in 2012, 29.6% in 2013. Medical record data at Puskesmas Pedes early detection of cervical cancer by IVA examination as much as 17.8% in 2012, 19.7% of people in 2013. These data show that there has been an increase in Cervical Cancer Early Detection. But it still has not reached the target of an early cervical cancer detection program which is 80%. The purpose of this study is to know the factors related to the behavior of women of childbearing age in early detection of cervical cancer in the village in the early working area of Pedes Public Health Center, Karawang District in 2013. This study used analytical methods with Cross Sectional design. The sample of this study were married women of childbearing age. Sampling with multistage random sampling technique, on 130 respondents using the level of significance (p≤0.05). The results of the study found that as many as 32 respondents (24.6%) had done early detection of cervical cancer while 98 respondents (75.4%) did not do early detection of cervical cancer. Based on the results of statistical tests showed that the 6 variables studied obtained 4 variables meaningful and 2 meaningless variables. The meaningful variables are education variables p = 0.046 (p≤0.05), knowledge variables p = 0.008 (p≤0.05), socioeconomic variables p = 0.000 (p≤0.05) and family support p = 0.037 (p≤0.05) while the non-meaningful variables are age and distance to the place of health services. It is recommended that the puskesmas improve socialization regarding, risk factors and early detection of cervical cancer.